Rekontruksi Model Ekonomi Berkelanjutan Berbasis Sunnah Nabawiyah Sebagai Fondasi Ekonomi Modern Yang Beretika (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
economic model by utilizing the values of the Prophetic Sunnah as an ethical foundation. This model aims to create an economic system that is not only economically efficient, but also promotes justice, sustainability and the well-being of humanity. By integrating Islamic teachings, especially the values of the Prophetic Sunnah, into a modern economic framework, this article proposes a holistic solution to today's global economic challenges. the method used in this research is descriptive qualitative analysis, where the author collects data that is analyzed and formulated through words. The purpose of this research is to find out how much the role of the Prophetic Sunnah is on the economy, and how this Prophetic Sunnah can support a sustainable economy in Indonesia, to reduce poverty to realize an ethical modern economy. The results of this study indicate that the values of the sunnah nabawiyah can support the economy in Indonesia, one of which is the application of ZISWAF. In addition, applying the principles of Islamic economics can open a wider economic network. But in realizing this, of course, there are many obstacles from various parties, both government and society
Keywords: Ekonomi Berkelanjutan, Nilai-Nilai Sunnah Nabawiyah, Keadilan, Keberlanjutan, Sistem Keuangan Islami